Model Kinetika Reaksi Polimerisasi Toluen Diisosianat (Tdi) - Dietilen Glikol (Deg) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The addition polymerization of toluene diisocyanate (TDI) with diethylene glycol (DEG) forms a linear polyurethane and with an excess of isocyanate, branching on the linear polymer occurs as a result of secondary reaction The aim of this research was to study polymerization reaction of TDI -DEG by developing the model of nonideal system using activity concept, with the activity coefficient predicted using UNIFAC method_ TDI - DEG polymerization was carried out in a three necked flask as batch reactor equipped with a stirrer, thermometer,- sampling device, freezer, water bath, and voltage regulator. The DEG solution was put into the reactor and heated to the desired temperature. After the desired temperature had been reached, TDI solution was added and stirred rigorously. During the process, the temperature was kept constant using a water bath Samples were taken from the flask at particular time (before the gel point was reached) to determine the NCO concentrations. Experiments were carried out at temperature of 30, 35, 40, 45, and 50Â°C with a constant NCO to OH ratio of 1.5 and at the NCO to OH ratio of 1.0, 1.5, 20, 25, and 3.0 with a constant temperature of 30Â°C It can be concluded that both model I and model II predicted well the polymerization of TDI - DEG. The rate constants k1 were higher than k2, both in the first model (ideal system) and the second one (nonideal system). The relations between the rate constant and temperature are as follows : the first model (ideal system approach), k1 85.3576e-4051m (L/mol.â¤), with an average error of 0.79%, IQ = 6.20758e-3779â¢144/RT (L/mol.â¤), with an average error of 0.93%